ANALYSIS OF THE FINANCIAL PERFORMANCE OF FOOD AND BEVERAGE COMPANIES BEFORE AND DURING THE COVID-19 PANDEMIC IN INDONESIA - Kristyana Dananti,; Magdalena Nany,; Eunike Frentelina Gusmao, (International Journal of Social Science, 2022)
The food and beverage sector is considered to have the strongest resilience in the Covid-19 pandemic, because its existence is related to basic human needs. So it is very interesting to identify the factors that affect the financial performance of companies in this sector. A total of 18 food and beverage sector companies listed on the Indonesia Stock Exchange during the 2018-2020 period were taken by purposive sampling. The data were analyzed using multiple regression analysis, starting with testing the classical assumptions of the regression model. The results of the analysis show that simultaneously, size, free cash flow, debt policy, liquidity, growth and asset management have a significant effect on financial performance. Partially, free cash flow and asset management have a significant effect on financial performance, while size, debt liquidity and growth policies partially do not significantly affect the company's financial performance.